Longitudinal links between maternal directives, children’s engagement in family conversations, and child linguistic skills - Tulviste, Tiia; Tamm, Anni (Frontiers in Psychology, 2023)
Much research on mother-child verbal interaction has been inspired by and the results are in line with the Vygotskian views that children acquire language and culture-specific ways of using language through actively participating in daily conversations with adults. Supporting the Vygotsky’s concept of the ZPD, the facilitative features of such conversations have found to depend on the age/the level of child language skills, and interactional context. Most prior studies in this field have been done in English-speaking Western families and during the first years of children’s life. Because Estonian middle-class mothers have found to pay much more heed to controlling children than mothers from some other cultural background, we include the frequency of directives into features of mothers’ speech that might have an impact on child language development. Thus, the current study explored the relative contribution of different features of mother-child interaction (e.g., mothers’ vocabulary diversity, use of attentional and behavioral directives, wh-questions, and the amount of children’s talk) to children’s language skills using data collected at two timepoint 1 year apart in Estonian middle-class families. As a novel approach to this topic, the study also examined the extent to which mothers’ input features relate to children’s contribution to parent-child conversation. 88 children and their mothers participated at children’s’ ages 3;0 and 4;0. We observed mother-child interactions during a semistructured videorecorded toy play at home. Mothers reported children’s language skills via the ECDI-III. Children’s language comprehension and production were measured by the examiner-administered NRDLS. Although the results showed somewhat differential effects of various aspects of mothers’ speech to different measures of child language skills at two timepoints, the diversity of mothers’ speech was positively and mothers’ frequent use of directives negatively related to children’s language skills. At both ages, the diversity of mothers’ speech predicted the amount of children’s verbal contribution to conversations. The findings will be discussed in the light of Vygotskian and his followers’ theoretical views as well as the theories about child language development.